Evaluation of drug prescribing pattern based on World Health Organization drug use indicators in dermatology outpatient department of Injibara General Hospital, Northwest Ethiopia, 2024 - Tegegnie, Alemu Bezabih; Alene, Tamiru; Bogale, Habtamu Nega; Tamir, Workineh; Sineshaw, Meaza Molla (Frontiers in Medicine, 2025)
BackgroundIrrational use of medicines is a problem globally that soon needs to be addressed. According to estimates from the World Health Organization, almost half of all medications were improperly prescribed. This study aimed to assess the drug prescribing patterns based on World Health Organization drug use indicators in the dermatology outpatient department of Injibara General Hospital.MethodA facility-based retrospective cross-sectional study was conducted from August 15 to August 30, 2024, with 620 patient prescriptions issued at the dermatology outpatient department of Injibara General Hospital. All patient prescriptions dispensed from the dermatology outpatient department from April to July 2024 were included. A structured data collection tool adopted from the World Health Organization core medicine use indicator was used to collect data, and Statistical Package for Social Science version 27.1 was used for data analysis.ResultsAn average of 1.74 drugs per encounters was prescribed, with 21.6 and 3.1% of prescriptions being antibiotics and injections, respectively. Generics were used in 95.4% of prescriptions, and nearly 84% of drugs were prescribed from the Ethiopian essential-drug list.ConclusionThe World Health Organization’s recommended threshold for the average number of prescriptions prescribed per encounter was met, indicating proper prescribing practices that reduce polypharmacy. The percentage of encounters with antibiotics was within the World Health Organization’s value, which reflects that dermatologists are less likely engaging in irrational antibiotic prescriptions. Likewise, the World Health Organization’s recommendations for the percentage of encounters with injection was met, indicating an effort to minimize unnecessary use of injections by dermatologists, which can reduce complications associated with injection use. However, the World Health Organization’s guidelines for generic drug prescriptions were not met, suggesting that dermatologists are less likely to prescribe generic drugs, which can raise patient healthcare expenditures considerably. Prescriptions from the Ethiopian essential medicine list also fell short of World Health Organization’s standards, indicating a failure to follow established guidelines.